Respuesta :

Hey there!
This is a pretty long equation, but don't let it confuse you- it's full of like terms.
Let's clean up the right side by adding the 4x and the 2x:

6x+2=3x-7

We can subtract 3x from both sides:

3x + 2 = -7

Subtract two to both sides to get:

3x = -9

Finally, divide both sides by 3 to get:

x = -3

Hopefully this helps!

First, you should add your like-terms on the left side.
6x+2=3x-7
Then subtract 3x from 6x to get rid of the x on the right side.
3x+2=-7
After that, subtract two from -7.
3x=-9
Divide -9 by 3.
x=-3.